Togo: Politics, economy and society in 2014 - Dirk Kohnert (Africa Yearbook Volume 11: Politics, Economy and Society South of the Sahara in 2014, 2015)
The upcoming presidential election set for 2015 dominated political discussion. The ruling elite clearly lacked the will for constitutional and electoral reforms, which the opposition, civil society and international donors regarded as precondition for free and fair polls. The donor community nevertheless increased their aid because of concerns about growing instability and terrorism in the sub-region and Togo's role as a willing supplier of troops for UN-missions. Promising growth prospects were overshadowed by increasing poverty, inequality and youth unemployment. – – Die bevorstehenden Präsidentschaftswahlen im Jahr 2015 dominierten die politische Diskussion. Der herrschenden Elite fehlte eindeutig der Wille zu Verfassungs- und Wahlreformen, die Opposition, Zivilgesellschaft und internationale Geber als Voraussetzung für freie und faire Wahlen betrachteten. Die Gebergemeinschaft erhöhte dennoch ihre Hilfe aufgrund von Bedenken hinsichtlich wachsender Instabilität und Terrorismus in der Subregion und Togos Rolle als bereitwilliger Truppensteller für UN-Missionen. Vielversprechende Wachstumsaussichten wurden durch zunehmende Armut, Ungleichheit und Jugendarbeitslosigkeit überschattet.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2014; domestic policy; foreign affairs; socio-economic development; period under review 2014